2017
DOI: 10.1002/cam4.1057
|View full text |Cite
|
Sign up to set email alerts
|

Risk and associated risk factors of hospitalization for specific health problems over time in childhood cancer survivors: a medical record linkage study

Abstract: Childhood cancer survivors (CCS) experience higher hospitalization rates compared to the general population for neoplasms, circulatory diseases, endocrine/nutritional/metabolic diseases and eye disorders. We studied trends in hospitalization rates and associated patient and treatment‐specific risk factors for diagnosis subgroups among these four diseases. We performed medical record linkage of a ≥5‐year CCS cohort with national registers, and obtained a random reference sample matched on age, gender and calend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…We found that survivors experience significantly increased hospitalization rates, especially for endocrine conditions, and subsequent neoplasms. These results confirm previous studies, in which second neoplasms [13][14][15][16][24][25][26], endocrine conditions [14,15,24,26], conditions of the blood and blood forming organs [13,16,24,25] and cardiovascular conditions [14,15,26] were shown to lead to hospitalizations in CCS. We extended these previous hospitalization investigations by showing that CCS experienced higher hospitalization rates for nearly all underlying types of conditions, and by investigating the treatment related determinants for each type of diagnosis leading to hospitalization in CCS in detail.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…We found that survivors experience significantly increased hospitalization rates, especially for endocrine conditions, and subsequent neoplasms. These results confirm previous studies, in which second neoplasms [13][14][15][16][24][25][26], endocrine conditions [14,15,24,26], conditions of the blood and blood forming organs [13,16,24,25] and cardiovascular conditions [14,15,26] were shown to lead to hospitalizations in CCS. We extended these previous hospitalization investigations by showing that CCS experienced higher hospitalization rates for nearly all underlying types of conditions, and by investigating the treatment related determinants for each type of diagnosis leading to hospitalization in CCS in detail.…”
Section: Plos Onesupporting
confidence: 92%
“…These results add important insight to previous literature, in which only radiotherapy to the head/neck was found to be a determinant for hospitalizations for endocrine conditions. [26] For hospitalizations because of subsequent neoplasms we identified cranial, abdominopelvic, and lower extremity radiotherapy and treatment with epipodophyllotoxins (which include teniposide and etoposide) as determinants. Although epipodophyllotoxins have well-established leukemogenic properties [27,28]; they were not associated with risk of subsequent malignant neoplasms in previous analyses in our cohort.…”
Section: Plos Onementioning
confidence: 99%
“…In long-term morbidity research in CCS, a broad variety of outcome assessment methods is used. Long-term morbidity outcomes can be assessed by self-reporting via questionnaires [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], by medical evaluation during outpatient clinic visits [25][26][27][28][29][30][31][32][33][34] or by linkage with existing registries such as national hospital discharge registries [35][36][37][38][39]. Authors often include different types and different numbers of organ systems in their calculations of physical long-term morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…We decided not to focus on the burden of hospitalizations, because hospitalizations represent health conditions for which survivors need intensive medical care and thus important, less severe conditions managed in the outpatient setting might be missed. As a result, several important papers on hospitalizations in survivors, for example, from the Adult Life after Childhood Cancer in Scandinavia study and from the DCOG‐LATER study were not included 70‐72 . A future systematic review should investigate the methods featured in publications reporting hospitalizations in long‐term childhood cancer survivors.…”
Section: Discussionmentioning
confidence: 99%